A young patient complaining of left scrotal pain diagnosed with testicular ischemia: a potentially fatal consequence of epididymitis - Manuela Montatore; Marina Balbino; Giacomo Fascia; Ruggiero Tupputi; Federica Masino; Gianmichele Muscatella; Rossella Gifuni; Giuseppe Guglielmi (Digital Diagnostics)
Rare complications of acute epididymitis include ischemia and infarction of the testicles. Both clinically and radiologically, it is challenging to distinguish testicular torsion. In this article we have tried to expand the library of digital images of radiological diagnostic methods used for fast and accurate differential diagnostics. This case emphasizes the significance of a comprehensive radiological assessment and how a multidisciplinary approach is necessary to guarantee an accurate diagnosis. A 24-year-old man experienced severe left testicular pain and came to the hospital 2 weeks later. At the radiology department, he reported that he had for some time painful ejaculations, pain during intercourse (dyspareunia), scrotal redness/swelling, genital inflammation, chills, swollen inguinal lymph nodes, dysuria, and scrotal pain. All diagnostic procedures were performed, first ultrasonography and then magnetic resonance imaging, as required by the urologist. The imaging studies revealed left testicular ischemia, and based on the referred clinical history, a chronic orchid-epididymitis was suspected. Thus, the condition was resolved, not with a left orchidectomy but with medical therapy because the ischemia area was not too large. The patient also had a left varicocele. Images acquired with different magnetic resonance imaging sequences were carefully examined. A rare instance of epididymal orchitis is described as a potentially dangerous complication of epididymitis and must be considered if sudden, severe scrotal pain is experienced to avoid severe consequences. This case can help with optimal patient management and prevent unnecessary interventions.